Development of an E-Pocketbook to Develop Critical Thinking Skills and Problem-Solving Ability - Wiyono, Cammelia; Baiduri, Baiduri; Zukhrufurrohmah, Zukhrufurrohmah (Universitas Muhammadiyah Mataram, 2023)
Learning by utilizing technology-based media that is easy to use and attractive to students is necessary in this era. However, technology in school learning still uses static PowerPoint media, which is less attractive to students. Therefore, it is necessary to develop e-pocketbook media as an alternative learning media that is interesting and easy for students. This study aims to: (1) Describe the validity of developing E-Pocketbook media to develop critical thinking skills and problem-solving abilities; (2) Describe the effectiveness of developing E-Pocketbook media to develop critical thinking skills and problem-solving abilities; and (3) Describe the practicality of the development of E-Pocketbook media to develop critical thinking skills and problem-solving abilities. The research was conducted at SMPN 1 Batu with 22 class VIII students as subjects. The characteristics of critical thinking skills and problem-solving abilities are classified as low because the learning media is less supportive. This research is a type of development research (Research and Development) using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The approach used is a qualitative descriptive method approach. The results of this study are that e-pocketbooks get a validity value that fulfills the 'valid' category, namely 79.77.91% for media, the value of effectiveness that meets the 'effective' category according to the n-gain test is 0.87 for critical thinking skills, and 0.84 for problem-solving, the value of practicality that fulfills the 'practical' category is 87.22%.